2020
DOI: 10.1136/jclinpath-2020-206946
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatic approach to assess SARS-CoV-2 protein S epitopes recognised by the most frequent MHC-I alleles in the Brazilian population

Abstract: AimsBrazil is nowadays one of the epicentres of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic and new therapies are needed to face it. In the context of specific immune response against the virus, a correlation between Major Histocompatibility Complex Class I (MHC-I) and the severity of the disease in patients with COVID-19 has been suggested. Aiming at better understanding the biology of the infection and the immune response against the virus in the Brazilian population, we analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
(31 reference statements)
0
11
0
1
Order By: Relevance
“…HLA-C is another example of a candidate for mediating COVID-19 severity since specific HLA subtypes have been associated with susceptibility for many viral infections, including HIV, HBV, H1N1, HCV and HPV [36] . From a functional standpoint, HLA-C is involved in both innate and adaptive immunity, but most importantly, HLA-C haplotypes have also been linked to the clinical course of COVID-19 [37] , [38] , [39] , [40] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA-C is another example of a candidate for mediating COVID-19 severity since specific HLA subtypes have been associated with susceptibility for many viral infections, including HIV, HBV, H1N1, HCV and HPV [36] . From a functional standpoint, HLA-C is involved in both innate and adaptive immunity, but most importantly, HLA-C haplotypes have also been linked to the clinical course of COVID-19 [37] , [38] , [39] , [40] .…”
Section: Resultsmentioning
confidence: 99%
“…However, as also occurred with AIM2, the overactivation of HLA-C can cause autoimmune reactions and the excessive release of cytokines leading to an exacerbated immune response. In this regard, HLA-C genetic variants are known to be associated with COVID-19 clinical outcome [37] , [38] , [39] , [40] . Importantly for the natural history of COVID-19 infection, GWAS have also shown that HLA-C constitutes a susceptibility locus for human pneumonia [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although immunogenic epitopes in both the structural and non-structural proteins of SARS-CoV-2 that could interact with the MHC-I alleles were identified [ 128 , 129 ], the role of immunoproteasome in SARS-CoV-2 infection specifically remains to be investigated. While it might be seminal to elicit an anti-viral adaptive response in the site of infection, it is likely that during the late phases of infection, when a cytokine storm takes place, the immunoproteasome might be strongly and persistently recruited to promote an excessive immune reaction fueling autophagy impairment.…”
Section: What We Know Do Not Know and What We Can Hypothesize Onmentioning
confidence: 99%
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] ...…”
Section: Uncited Referencesunclassified